Implementation Of Project-Based Learning Based On Computational Thinking To Prepare Private Senior High School Students In East Jakarta As The Golden Generation Of 2045 - Wardani, Febri Pramudya; Sundari, Sri; Suharyono, Suharyono; Pakpahan, Marisi (STABN RADEN WIJAYA WONOGIRI, 2024)
Improving the quality of education is essential to shaping Indonesia's Golden Generation 2045, characterized by excellence, innovation, and global competitiveness. This study focuses on implementing Project-Based Learning (PBL) integrated with Computational Thinking (CT) in private high schools in East Jakarta as a strategic approach to bridge the gaps in access and education quality. The approach emphasizes not only theoretical aspects but also contextual project-based learning that fosters 21st-century skills development.The key issues addressed include disparities in educational access and quality across various schools at both national and local levels, as identified through global indicators. These challenges highlight the need for educational interventions that enhance student competitiveness by applying adaptive and innovative curricula. Computational Thinking is employed to train students in systematic thinking, problem-solving for complex challenges, and innovation through technological applications.This research aims to analyze the effectiveness of Project-Based Learning combined with Computational Thinking in improving student outcomes, creativity, and adaptive skills. The findings are expected to provide strategic recommendations for developing education policies based on innovation, thereby addressing global educational challenges and enhancing the quality of private schools in Indonesia